Songket Aesan Gede Sebagai Pakaian Adat Perkawinan Tradisional Palembang (1966-1986) - Supriyanto Supriyanto; Novika Ratna Sari (Criksetra: Jurnal Pendidikan Sejarah, 2017)
This study entitled "Songket Aesan Gede As Traditional Clothing Traditional Marriage Palembang Year 1966-1986 (Donations Material for Teaching History at Junior High School 33 Palembang)". The issues examined are 1. How ordinances marriage customs of society in Palembang during 1966 - 1986. 2. How Songket privilege to serve as a Gede Aesan Traditional Clothing Traditional Marriage Palembang. 3.What is the significance of motifs and colors of songket Aesan Gede thus serve as a Traditional Clothing Traditional Marriage Palembang. The purpose of this study to determine 1. Explain the information about the Customary Marriage Palembang to the public, especially the younger generation. 2.Explaining how special the traditional custom clothing Aesan Gede to withstand up to sek charcoal. 3.Explaining the meaning of the information about the motifs and colors of songket Aesan Gede thus serve as a Traditional Clothing Traditional Marriage Palembang. The method used in this research writing that Historical method with steps that include heuristic, Source Criticism, Interpretation, and Historiography. Historiography is done through a literature search and interview research methods The results of this study are as follows: the development of culture in one place can be seen from the traditional wedding ceremony. This can be evidenced by the differences that occur in every traditional wedding ceremony from one period to another.And cultural influences from outside that makes people increasingly want to make things easier and instantaneous, and the development of an area it will be many colorful combinations of every Clothing Traditional Palembang area of progress more rapidly.